(untitled) (Latakia University Journal -Basic Sciences Series, 2018)
تم في هذا البحث دراسة التأثيرات المتبادلة بين كلوريد البيريليوم وكلوريد التوتياء في وسط المحل العضوي ثنائي ايتيل الايتر (Et2O: Diethyl Ether). ترافقت هذه التأثيرات بارتفاع درجة حرارة المزيج التفاعلي في الجملة المدروسة، وتم دراسة التوازنات الطورية وشروط تشكل المركبات المعقـدة الايترية لكلوريـدات البيريليوم والتوتياء في الجملـة الثلاثيـة: BeCl2 – ZnCl2 – Et2O عند درجة الحرارة 25 oC وفقا للتفاعل التالي: x c ودرست أيضا الشروط اللازمة لفصل المركبات المعقدة المتشكلة عن جملها، وكذلك بعض خواصها الفيزيائية والكيميائية بواسطة IR-Spectroscopy. أظهرت الدراسة أن تشكل المركبات المعقدة بين كلوريد البيريليوم وكلوريد التوتياء في وسط المحل Et2O حدث في الشروط العادية )زمن حدوث التفاعل، سرعة التحريك الدوراني ودرجة الحرارة(، وأن الصيغة المجملة العامة للمركبات المتشكلة هي: a BeCl2 . b ZnCl2 . n Et2O حيث (a, b, n) أعداد صحيحة. وكذلك أظهرت الدراسة الطيفية أن المركبات تحتوي على روابط تساندية M – O، حيث M = Be, Zn، وجسور كلورية. The interactions between beryllium chloride and zinc chloride in the medium of the organic solvent diethyl ether (Et2O) were studied. These effects were accompanied by elevation of the temperature of the mixture in the system under study. The paper also studied the phase balances, and the formation conditions of compounds in the following tri-system: BeCl2 – ZnCl2 – Et2O at T = 25 oC, according to the following reaction: The conditions required for separating the compounds formed in their systems were studied. Some of the physical and chemical properties of complexes had been studied, using IR-Spectroscopy. This study demonstrated that the formation of complex compounds between BeCl2 and ZnCl2 in a medium Et2O occurred in normal conditions (time of occurring reaction, speed of circulatory movement and temperature), the chemical formula is consequently: a BeCl2 . b ZnCl2 . n Et2O. The spectroscopic study also showed that the complex compounds were formed with coordinate bonds M – O, where M = be and Zn, and chloride bridges.